PENGARUH MEDIA BOOKLET TERHADAP PENGETAHUAN TENTANG SYOK HIPOGLIKEMIA - siti romadoni (IKesT Muhammadiyah Palembang, 2024)
Introduction: Diabetes mellitus (DM) is a chronic metabolic disease or disorder with multiple etiologies characterized by high blood sugar levels accompanied by impaired carbohydrate, lipid, and protein metabolism as a result of insulin function insufficiency. Indonesia itself is ranked 7th with the number of DM sufferers reaching 7.6 million people. DM sufferers in everyday life always face high blood sugar conditions. However, DM sufferers can actually experience a drastic decrease in blood sugar levels or better known as diabetic shock or hypoglycemic shock. Undetected hypoglycemia can cause conditions that endanger the sufferer. Objective: to determine whether there is an effect of booklet media on knowledge about hypoglycemic shock. Method: The type of research is Pre-Experimental with the One Group Pretest and Posttest Design approach. The sample was taken by accidental sampling totaling 30 respondents in DM patients at the Internal Medicine Polyclinic of RSMP. The instrument used was a questionnaire about knowledge. The analysis used was the Paired T Test. Results: The mean value of respondents' knowledge before being given the booklet media was 15.87 and after being given the booklet media increased to 20.67. The results of the T test obtained a p value = 0.000 (p <0.05). Discussion: There is an influence between the provision of booklet media on knowledge about hypoglycemic shock. Keywords: Booklet, Hypoglycemic Shock.